Victim Oriented Plea Bargaining in Indonesia’s Criminal Justice System : Toward Substantive Justice for Victims of Crime - Rizkianto, Kus; Rahayu, Kanti; Nunna, Bhanu Prakash (Universitas Muhammadiyah Purwokerto, 2026)
This study examines the formulation of a victim-oriented plea bargaining model to promote substantive justice for both defendants and victims in Indonesia. Plea bargaining refers to a defendant’s admission of guilt through negotiation with the public prosecutor in exchange for a reduced sentence. It may be applied to first-time offenses punishable by a maximum imprisonment of five years and a maximum fine of five hundred million rupiah, provided that the defendant agrees to compensate the victim. However, judicial practice shows that plea bargaining tends to prioritize imprisonment while neglecting victims’ rights to restitution. Using a normative juridical method, this study analyzes statutory regulations and legal literature through qualitative descriptive analysis. The findings reveal two main issues. First, plea bargaining is regulated under Article 78 paragraph (1), Article 205 paragraph (2), and Article 234 paragraph (1) of Law Number 20 of 2025 concerning the Criminal Procedure Code, but non-compliance with restitution obligations only results in substitute imprisonment, leaving victims uncompensated. Second, a victim-oriented model should require defendants to apologize, involve victims in negotiations, and ensure agreement on compensation, settlement mechanisms, and criminal sanctions. When defendants are unable to provide compensation, the State should assume responsibility through a victim compensation fund. This study recommends revising the Criminal Procedure Code, establishing state-funded victim compensation, strengthening prosecutorial supervision over plea bargaining agreements, and formulating Supreme Court guidelines to balance defendants’ rights with victims’ substantive justice.